Sistem Pendukung Keputusan Dalam Pemilihan Supplier Kopi Menerapkan Metode OCRA Dengan Pembobotan ROC - Novyanti Chandra; Afifah Trista Ayunda (Universitas Islam Raden Rahmat, Malang, 2023)
The coffee business has been experiencing rapid growth, leading coffee business operators to seek high-quality coffee supplier that can meet the needs of their customers. The selection of a coffee supplier is crucial, as it can help maintain customer loyalty. However, often, issues arise in the supplier selection process, such as managing complex information, conducting evaluations, and still relying on manual selection methods. Therefore, a decision support system is needed to provide accurate and quick decisions using the Operational Competitiveness Rating Analysis (OCRA) method and weighting generated from the Rank Order Centroid (ROC) method. The determination of the coffee supplier involves 5 criteria such as price, coffee quality, roasted level variation, aroma, and location. The results of the assessment using the Operational Competitiveness Rating Analysis (OCRA) and Rank Order Centroid (ROC) methods identify the best alternative as the coffee supplier, which is named The Cold Crafters with a preference score of 1.2453.